Increasing Customer Loyalty through Strengthening Digital Banking and Customer Relationship Management with Customer Satisfaction as an Intervening Variable (Case Study at PT. Bank Negara Indonesia (Persero) Tbk Cibinong Branch Office). - Wati, Juni Lamria; Muharam, Hari; V. Purba, Jan Horas (Budapest International Research and Critics University, 2024)
Research related to customer loyalty shows that customer satisfaction greatly influences customer loyalty both directly and indirectly. The aim of this research is to test and reveal empirically the factors that influence customer loyalty, both direct factors, namely Digital Banking and Customer Relationship Management and indirect factors, namely customer satisfaction. This research was conducted at the BNI Cibinong Branch Office which consists of the Main Branch, 4 sub-branch offices and 2 cash offices under the management of KC Cibinong and used quantitative data (from questionnaires). The research sample consisted of 125 emerald BNI KC Cibinong customers. SEM analysis is used to determine the influence between research variables. The research results show, 1) There is a positive and significant influence of Digital Banking on Customer Loyalty, 2) There is a positive and significant influence of Customer Relationship Management on customer loyalty, 3) There is a positive and significant influence of customer satisfaction on customer loyalty, 4) There is a positive and significant influence of Digital Banking has a significant impact on customer satisfaction, 5) There is a positive and significant influence of Customer Relationship Management on customer satisfaction, 6) There is a positive and significant influence of Digital Banking on customer loyalty through customer satisfaction and 7) There is a positive and significant influence of Customer Relationship Management on customer loyalty through customer satisfaction. This research proposes several recommendations for strong indicators that have a high contribution to Digital Banking, Customer Relationship Management and customer satisfaction in order to increase customer loyalty.